Mediating Effects of Cash Management in Relationship Between Capital Structure and Liquidity in Small and Medium Enterprises - Danjuma, Ibrahim; Umar, Mohammed Sangiru; Hammawa, Dahiru Dauda (International Journal of Economics and Financial Issues, 2015)
This study attempts to establish the relationship that exists between capital structure, cash management and liquidity in some selected small and medium enterprises in Jimeta, Adamawa state. It also determines the mediating effect of cash management in the association of capital structure and liquidity. A total of 365 copies of questionnaires were administered to 366 small and medium scale enterprise but a total 310 copies of questionnaires were returned fully and appropriately filled. The study made use of but primary and secondary method in collecting data. A cluster sampling method was used in this study and purposive sampling was also used to choose units of analysis in all clusters. Descriptive and inferential statistic such as frequencies mean, and standard deviation including Pearson’s correlation coefficient, multiple regression and sobel test were employed to obtain results. The results indicate that there is a positive significant relationship between capital structure and cash management, capital structure and liquidity, liquidity and cash management at a correlation of 0.657, 0.657 and 0.640 respectively, significant at 0.01 level (2-tailed) and df= 309. To support the correlation analysis, the regression analysis was also used to see the variability in the relationship and it indicates that 43.1% and 43% of the variability in both cash management and liquidity can be explained by the capital structure of the firm and also 41% of the variability in liquidity can be explained by cash management. The sobel test and the Kenny and Baron approach were used to test the mediating effect of cash management in the relationship between capital structure and liquidity and it indicate a partial mediation between the variables. A single research methodology approach was used and the findings from this research are cross sectional, future research through other methods could be undertaken to triangulate and also should be taken across time. The study recommends that chief financial officers exercise caution while choosing the amount of debt to use in their capital structure since a positive relationship exist between capital structure, liquidity and cash management. Keywords: Capital Structure; Cash Management; Liquidity; Mediation JEL Classifications: G3; J52